Pengaruh Pendapatan Asli Daerah dan PDRB terhadap Belanja Daerah dan Indeks Pembangunan Manusia di Provinsi Aceh - Fani Fadillah; Fatma Erwita; Fatimah Azzahra; Lutfhia Regina Jambak; Risa Yolanda (Jurnal Sociohumaniora Kodepena (JSK), 2023)
This study aims to examine how regional spending and the Human Development Index in Aceh province are influenced by Regional Native Income and Gross Regional Domestic Product. Using secondary data, this study was conducted in Aceh Province. The purpose of this study is to determine the relationship between Regional Native Income (PAD) and GRDP with Regional Expenditure (BD) and the Human Development Index in Aceh Province. Path analysis using Eviews software version 12 is a data analysis technique used in this study. The findings of the study show that simultaneously [1] Regional Native Income and GRDP have no visible impact on regional spending. [2] Local Revenue and GRDP have a considerable influence on the Aceh Provincial Human Development Index.